2011
DOI: 10.1002/cne.22729
|View full text |Cite
|
Sign up to set email alerts
|

Cellular, biochemical, and molecular characterization of nitric oxide synthase expressed in the nervous system of the prosobranch Stramonita haemastoma (Gastropoda, Neogastropoda)

Abstract: Nitric oxide synthase (NOS) has been characterized in several opistobranchs and pulmonates but it was much less investigated in prosobranchs, which include more than 20,000 species and account for most of the gastropod diversity. Therefore, new data from this large group are needed for a better knowledge of the molecular evolution of NOS enzymes in molluscs. This study focused on NOS expressed in the nervous system of the prosobranch neogastropod Stramonita haemastoma. In this study we report compelling eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 75 publications
3
18
0
Order By: Relevance
“…NOS is the most crucial component of the NO system as a result of its exclusive role in the de novo synthesis of NO, and this enzyme synthesizes large amounts of NO when participating in or modulating the immune defenses of both vertebrates and invertebrates (10)(11)(12)41). Thus far, several NOS genes have been cloned and characterized in invertebrates (38,(49)(50)(51)(52), whereas their diversity and phylogeny remain nearly unexplored. In the present study, the molecular characterization of oyster NOS and its activation in the immune response were investigated to develop a better understanding of the phylogenetic evolution of NOS and its immunomodulation in molluscs.…”
Section: Discussionmentioning
confidence: 99%
“…NOS is the most crucial component of the NO system as a result of its exclusive role in the de novo synthesis of NO, and this enzyme synthesizes large amounts of NO when participating in or modulating the immune defenses of both vertebrates and invertebrates (10)(11)(12)41). Thus far, several NOS genes have been cloned and characterized in invertebrates (38,(49)(50)(51)(52), whereas their diversity and phylogeny remain nearly unexplored. In the present study, the molecular characterization of oyster NOS and its activation in the immune response were investigated to develop a better understanding of the phylogenetic evolution of NOS and its immunomodulation in molluscs.…”
Section: Discussionmentioning
confidence: 99%
“…In mollusks, NOSs have been identified in the red‐mouthed rock shell (Cioni et al. ), great pond snail (Korneev et al. ), California sea hare (Sadreyev and colleagues, abstract), greenhouse slug (Matsuo and Ito ), common cuttlefish (Scheinker et al.…”
Section: Discussionmentioning
confidence: 99%
“…In mollusks, NOSs have been identified in gastropods, including the red‐mouthed rock shell Stramonita haemastoma (Cioni et al. ), great pond snail Lymnaea stagnalis (Korneev et al. ), California sea hare Aplysia californica (R. I. Sadreyev, Y. Panchin, P. Uvarov, A. Belyavski, and M. Matz, abstract presented at the Society for Neuroscience, 2000), and greenhouse slug Limax valentianus (Matsuo and Ito ); in a cephalopod, the common cuttlefish Sepia officinalis (Scheinker et al.…”
mentioning
confidence: 99%
“…The highest expression level of CfNOS mRNA was observed in the gonad, indicating that NO might be able to regulate scallop gametogenesis and/or steroidogenesis [16,18]. Relative higher level of CfNOS transcripts was expressed in the mantle, which suggested the possible role of NO system in sensory process [21]. In addition, as hepatopancreas and haemocytes are most important immune tissues in mollusc, the CfNOS transcripts in these tissues indicated that CfNOS might be involved in scallop immune responses [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there was only one NOS gene in Drosophila genome [14], which could be transcribed into multiple alternative RNA splicing variants [15], and a single copy of NOS ortholog was characterized from crustaceans [1620]. In mollusc, NOSs were identified in the gastropods Stramonita haemastoma , Lymnaea stagnalis , Aplysia californica and Limax valentianus , the cephalopod Sepia officinalis , and the bivalve Crassostrea gigas and Crassostrea virginica [2126], and all the identified NOSs belonged to one isoform which had higher similarities with nNOS than eNOS or iNOS from vertebrates. Though the composition of NOS family and the differentiation of NOS members in invertebrates were different from those in vertebrates, invertebrate NOSs had resembled broad involvements in various physiological activities.…”
Section: Introductionmentioning
confidence: 99%